2017
DOI: 10.1063/1.4993427
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced radiative emission from monolayer MoS2 films using a single plasmonic dimer nanoantenna

Abstract: By thinning transition metal dichalcogenides (TMDCs) to monolayer form, a direct bandgap semiconductor emerges which opens up opportunities for use in optoelectronic devices. However, absorption and radiative emission is drastically reduced which hinders their applicability for practical devices. One way to address this challenge is to design plasmonic resonators that localize electric fields within or near the two-dimensional (2D) material to confine excitation fields and increase Purcell factors. Previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 37 publications
1
29
1
Order By: Relevance
“…Several different strategies have also been employed to intensify and tune the photoluminescence (PL) from 2D TMDs. Chemical treatments [29][30][31], alloying [32][33][34][35], coupling with surface plasmon polaritons [36,37], integration with photonic crystal cavities [38,39], and strain engineering [40] are some of these proposed methodologies to improve the band-to-band PL characteristics of 2D TMDs. Moreover, it is found that a strong sub-band-gap PL can be originated from defect-mediated transitions [23,25,[41][42][43][44][45][46] that are of great interest in the design of NIR LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Several different strategies have also been employed to intensify and tune the photoluminescence (PL) from 2D TMDs. Chemical treatments [29][30][31], alloying [32][33][34][35], coupling with surface plasmon polaritons [36,37], integration with photonic crystal cavities [38,39], and strain engineering [40] are some of these proposed methodologies to improve the band-to-band PL characteristics of 2D TMDs. Moreover, it is found that a strong sub-band-gap PL can be originated from defect-mediated transitions [23,25,[41][42][43][44][45][46] that are of great interest in the design of NIR LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the highly efficient growth by chemical vapor deposition (CVD) is promising to meet the demand of mass production 11 . Benefiting from these advantages, TMDCs offer a unique platform for investigation of intriguing light-matter interactions at the nanoscale through, besides the well-known van der Waals heterostructures 12,13 , the integration with artificial materials, such as photonic nanocavities 14,15 , plasmonic nanostructures 16 , and single nanoparticle antennas 17 . This enables the establishment of compact optoelectronic devices, including tunable light emitters 18 , nanolasers 19,20 , electro-optic modulator 21 , optical switches 22 , biosensors/detectors 23,24 , fieldeffect transistors 25 , quantum devices 26 , etc., which are the key elements of the next-generation integrated photonic circuits.…”
mentioning
confidence: 99%
“…It is, therefore, essential to couple these 2D planes with light-trapping schemes that obtain broad and strong light absorption. As stated previously, strong, near-field coupling using plasmonic nanounits is one of these solutions [54], [55]; however, this article aims to summarize the planar multilayer trapping strategies. The proper architecture for light absorption in these 2D semiconductors is to couple them into 1D photonic crystals (PCs).…”
Section: Lithography-free Multilayer Perfect Absorbersmentioning
confidence: 99%